FELDMEIER, Reinhard; SPIECKERMANN, Hermann. O Deus dos Vivos: uma doutrina bíblica de Deus. São Leopoldo: Sinodal, 2015. - Sell, Wilhelm (Vox Scripturae - Revista Teológica Internacional, 2016)
FELDMEIER, Reinhard; SPIECKERMANN, Hermann. O Deus dos Vivos: uma doutrina bíblica de Deus. São Leopoldo: Sinodal, 2015.